Pengaruh Modul Elektronik Terhadap Self-Regulated Learning dan Hasil Belajar Kognitif Pada Materi Ikatan Kimia - Anugrah Anang Respati; Sri Atun (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to the effect of guided inquiry-based electronic modules on self-regulated learning and cognitive learning outcomes. The research design uses a quasi-experimental post-test only. This research was conducted on students of class X Natural Science in Yogyakarta using the cluster random sampling technique. The instrument used in this research is a self-regulated learning questionnaire and cognitive learning outcomes test. The data analysis technique uses Hotelling’s T-Test to test whether there are differences in self-regulated learning and cognitive learning outcomes with the implementation of electronic modules. The results show that the significance value is 0.002 < 0.05. This means that there is a difference in self-regulated learning and cognitive learning outcomes between students who use the guided inquiry-based electronic module and those who do not use the electronic module.